STUDI KOMPARASI PENGGUNAAN AC KESET DAN AC SPLIT DALAM GEDUNG GRIYA LEGITA UNIVERSITAS PERTAMINA - Meredita Susanty; Aditya Dewata Putra; Laras Ijmania Kusuma; P. B. Ebelaristra; Refal Pradama Dahlan; Vicky Sultan Ahmad (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
Air Conditioning is one of the most energy-consuming infrastructure in a building, which makes it one of the things that an asset manager needs to pay special attention to. This research uses comparative method that compares the current AC usage scenario in Universitas Pertamina’s Griya Legita Building, which currently uses both split AC and cassette AC, with a scenario where the whole building only uses either split AC or cassette AC. The calculation shows that, although the first-year investment for new AC installation costs more than the current scenario, the scenario where the whole building uses only split AC is proven to be a more cost-efficient investment in the long run. The result of this research is an important asset for the asset manager of Universitas Pertamina to consider in order to save energy consumption cost in Universitas Pertamina.